Prezydent w systemie politycznym Rosji : rozwiązania prawne i praktyka polityczna - Kużelewska, Elżbieta (Wydawnictwo Uniwersytetu Wrocławskiego, 2021)
The president’s strong position in Russia’s political system results from two important factors. First of all, these are constitutional and legal solutions that equip the president with a range of powers of his own and those of other authorities, making the head of state office almost hegemonic. Secondly, these are extra-legal factors, the so-called personality factors, assigned to individual Russian presidents who exercised power under almost on the same legal regulations and very similar competences. However, the presidencies of Yeltsin, Medvedev, and Putin were very different. The article analyzes the thesis that until March 2020, the strong position of the Russian president was not only legal, but also “personal.” The announced amendment of the Constitution in 2020 in terms of counting the president’s new term of office means Putin’s attempt to give priority to legal regulations, which in consequence will allow the extension of his rule in the majesty of the law and will not allow a system of “two powers.”
Keywords: Federacja Rosyjska; głowa państwa; Putin, Vladimir; prezydent; władza wykonawcza